Inflation Targeting and Inflation Expectations: Evidence for Brazil and Turkey - Sumru Altuğ; Cem Çakmaklı (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
In this paper, we study the evolution of inflation expectations for two key emerging economies, Brazil and Turkey, using a reduced form model in a state-space framework, where the level of inflation is modeled explicitly. We match the survey-based inflation expectations and inflation targets set by the central banks of Brazil and Turkey with the predictions implied by the model in a statistically coherent way. Confronting these expectations with inflation targets leads to a statistical measure of the discrepancy between inflation expectations and the target inflation. The results indicate that inflation expectations are anchored more closely the inflation target set by the Central Bank for Brazil. By contrast, there is more evidence that inflation expectations deviate significantly from the target inflation set by the Central Bank for Turkey.
Keywords: E31; E37; C32; C51; 330; Inflation targeting; survey-based inflation expectations; forecasting; state space model